2000
DOI: 10.1210/jcem.85.10.6917
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition, Blood Pressure, and Lipid Metabolism before and during Long-Term Growth Hormone (GH) Treatment in Children with Short Stature Born Small for Gestational Age Either with or without GH Deficiency1

Abstract: To assess the effects of long-term continuous GH treatment on body composition, blood pressure (BP), and lipid metabolism in children with short stature born small for gestational age (SGA), body mass index (BMI), skinfold thickness measurements, systemic BP measurements, and levels of blood lipids were evaluated in 79 children with a baseline age of 3-11 yr with short stature (height SD-score, ϽϪ1.88) born SGA (birth length SD-score, ϽϪ1.88). Twenty-two of the 79 children were GH deficient (GHD). All children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…Nevertheless, the observed changes in lipid profiles were consistent with previous studies where it was concluded that GH treatment could have beneficial effects on lipid metabolism in children with short stature born SGA [12]. Such studies also indicated that lipid alterations were not related to the onset of puberty [18].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Nevertheless, the observed changes in lipid profiles were consistent with previous studies where it was concluded that GH treatment could have beneficial effects on lipid metabolism in children with short stature born SGA [12]. Such studies also indicated that lipid alterations were not related to the onset of puberty [18].…”
Section: Discussionsupporting
confidence: 90%
“…There was no significant difference between the treatment groups for either systolic BP (treatment difference -3.7, CL -10.7, 3.4; 67 vs. 33 µg/kg/day group, 260 weeks vs. baseline) or diastolic BP (treatment difference -3.4, CL -10.2, 3.4; 67 vs. 33 µg/kg/day group, 260 weeks vs. baseline). Despite the observed increases, systolic and diastolic BP measurements did not exceed normal limits for healthy children, and the subjects in this study were considered normotensive [12,18,19]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies include data of de Zegher et al [11, 12], Sas et al [13, 14]and several other groups. The de Zegher and Sas studies essentially evaluated the effects of two doses of continuous GH treatment over 5–6 years.…”
Section: Treatmentmentioning
confidence: 99%
“…Similarly, the group of Azcona et al [15] using a lower dose of GH (0.3 mg/kg/week) failed to show a difference between the GH-sufficient and -insufficient group, although each had a response less than those in the studies employing higher doses. Thus, the degree of GH sufficiency did not appear to predict the response either to traditional or higher doses of GH [11, 12, 13, 14, 15, 16]. …”
Section: Treatmentmentioning
confidence: 99%